Pancreatic Acinar Cells: Molecular insight from studies of signal-transduction using transgenic animals - Yule, David I. (2010)
Pancreatic acinar cells are classical exocrine gland cells. The apical regions of clusters of coupled acinar cells collectively form a lumen which constitutes the blind end of a tube created by ductal cells-a structure reminiscent of a “bunch of grapes”. When activated by neural or hormonal secretagogues, pancreatic acinar cells are stimulated to secrete a variety of proteins. These proteins are predominately inactive digestive enzyme precursors called “zymogens”. Acinar cell secretion is absolutely dependent on secretagogue-induced increases in intracellular free Ca(2+). The increase in [Ca(2+)](i) has precise temporal and spatial characteristics as a result of the exquisite regulation of the proteins responsible for Ca(2+) release, Ca(2+) influx and Ca(2+) clearance in the acinar cell. This brief review discusses recent studies in which transgenic animal models have been utilized to define in molecular detail the components of the Ca(2+) signaling machinery which contribute to these characteristics.